2022
DOI: 10.1021/acsinfecdis.2c00402
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Substrate Scope of a Bacterial Nucleotidyltransferase via Allosteric Mutations

Abstract: Bacterial glycoconjugates, such as cell surface polysaccharides and glycoproteins, play important roles in cellular interactions and survival. Enzymes called nucleotidyltransferases use sugar-1-phosphates and nucleoside triphosphates (NTPs) to produce nucleoside diphosphate sugars (NDP-sugars), which serve as building blocks for most glycoconjugates. Research spanning several decades has shown that some bacterial nucleotidyltransferases have broad substrate tolerance and can be exploited to produce a variety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…Now, kinases have been identified for the phosphorylation of several common monosaccharides, such as D‐GalNAc, D‐GlcNAc, D‐Gal, D‐GlcA, D‐GalA, D‐Man, and L‐Fuc [4] . Recently, Lupoli and co‐workers reported that a nucleotidyltransferase from Salmonella enterica (SeRmlA) could recognize diverse phosphorylated monosaccharides, [41] indicating the potential for application in the large‐scale preparation of dTDP‐sugars.…”
Section: Resultsmentioning
confidence: 99%
“…Now, kinases have been identified for the phosphorylation of several common monosaccharides, such as D‐GalNAc, D‐GlcNAc, D‐Gal, D‐GlcA, D‐GalA, D‐Man, and L‐Fuc [4] . Recently, Lupoli and co‐workers reported that a nucleotidyltransferase from Salmonella enterica (SeRmlA) could recognize diverse phosphorylated monosaccharides, [41] indicating the potential for application in the large‐scale preparation of dTDP‐sugars.…”
Section: Resultsmentioning
confidence: 99%
“…With synthetic access to l -S-1Ps, we evaluated the substrate scope of engineered RmlA. As expected, incubation of RmlA* with α-Glc-1P, α-Man-1P, or β- l -Fuc-1P and dTTP (2 mM each) led to formation of the corresponding dTDP-sugars (Figure A). However, when the synthetic β- l -S-1Ps ( 3 – 5 ) or corresponding α- l- S-1Ps were incubated with dTTP under similar conditions, only β- l -Man-1P ( 4 ) was activated (Figure A,B), as confirmed by MS analysis (Figure C).…”
mentioning
confidence: 79%
“…Expanding on past work, we recently demonstrated that engineering of SALTY RmlA’s allosteric site leads to enhanced substrate promiscuity . Incorporation of the allosteric mutation E256D in a known active site mutant (Y146F) carrying the stabilizing alteration D104N also led to improvements in catalytic activity.…”
mentioning
confidence: 99%
“…Modification to the allosteric site permits enhanced activity and expanded substrate scope. Adapted and reproduced from ref ( 111 ). Copyright 2022 American Chemical Society.…”
Section: Using Biocatalysis To Provide the Building Blocks For Bioche...mentioning
confidence: 99%
“…As an alternative to bump-and-hole modifications of the active site, rational mutation of the allosteric site of the nucleotidyltransferase RmlA was recently demonstrated, leading to expanded substrate tolerance and improvements in catalytic activity. 111 RmlA is responsible for catalyzing the formation of dTDP- d -Glc from Glc-1-phosphate and deoxythymidine triphosphate in vivo. The catalytic efficiency of RmlA is limited by a negative feedback inhibition loop, through binding of dTDP- l -Rha to the allosteric site ( Figure 3 B).…”
Section: Using Biocatalysis To Provide the Building Blocks For Bioche...mentioning
confidence: 99%